Regional coordinators of Sao Paulo State prisons in tuberculosis and HIV coinfection care - Nanci Michele Saita; Daniele Maria Pelissari; Rubia Laine de Paula Andrade; Pedro Augusto Bossonario; Mariana Gaspar Botelho Funari de Faria; Antonio Ruffino Netto; Aline Aparecida Monroe
ABSTRACT Objectives: to analyze the care provided to individuals with Tuberculosis (TB)-HIV coinfection in prison units in the state of São Paulo, according to the regional coordination of prisons. Methods: cross-sectional study conducted between 2016 and 2018. A structured questionnaire was applied to 112 directors or health professionals from 168 prison units. Data were analyzed by frequency distribution and multiple correspondence analysis. Results: 92.9% of participants reported active search for respiratory symptoms, 89.3% offer the directly observed treatment (DOT) for all TB cases, 95.5% anti-HIV testing for all inmates, 92.9% offer HIV follow-up in specialized care services and 59.8% antiretroviral drugs for cases of coinfection. An association was identified between the Northwest and Central regional coordinations and deficient human resources and low performance of actions for the diagnosis and follow-up of cases. Conclusions: although most prison units perform planned actions for the care of coinfected persons, some places need support to guarantee access to these actions.